Transposons and Integrons: Natural Genetic Engineering of Bacterial Resistance - Paul H Roy (Canadian Journal of Infectious Diseases)
The advent of antibiotics in clinical medicine has resulted in the emergence of multiresistant strains of bacteria. Bacteria possess sophisticated mechanisms of genetic exchange that have driven their recent evolution. Among these are transposons and integrons, the latter having interesting parallels with genetic engineering techniques used in the laboratory. An understanding of these mechanisms through studies of the molecular basis of the dissemination of resistance genes will aid rational choices in antibiotic therapy.